Efektivitas Restorative Justice (RJ) dalam Penyelesaian Perkara di Lampung Utaral - Rifki Dwi Prasetya (Jurnal Hukum Lex Generalis, 2026)
Restorative justice is a recovery-oriented approach to resolving criminal cases involving perpetrators, victims and the community. This study aims to analyze the effectiveness and constraints of restorative justice implementation in North Lampung. The research method used is empirical juridical with a statutory and case-based approach. The results show that of 153 police reports in 2025, 23 cases (15.03%) were resolved through diversion/restorative justice mechanisms. Its implementation is quite effective in minor cases and juvenile cases, but still hampered by public understanding, limited apparatus, coordination, and technical regulations. Strengthening the capacity of officers and socialization are needed to optimize its implementation.